Land use in the areas of great flood hazard in Slovenia - Žiberna, Igor (Journal for Geography, 2014)
In the article, we analysed the land use in areas of great flood hazard in Slovenia in the year 2014. We mainly examined inappropriate land use in the areas of great flood hazard. We showed the trends in land use changes in the flood regions between the years 2000 and 2014 and analysed the trends in the municipalities mostly threatened by floods. Further on, we separately analysed the current state of land use in the flood region along Drava River in November 2012.